INVESTIGATING PHARMACEUTICAL AND THERAPEUTIC PRESCRIPTIONS OF CUTANEOUS LEISHMANIASIS IN DEHLORAN CITY DURING 2015: Pharmaceutical Sciences-Pharmacology - SHAHSAVARI, SOMAYEH; NASERIFAR, RAZI; FATOLLAHI, EBRAHIM; RAFIEIAN-KOPAEI, MAHMOUD (International Journal of Life Science and Pharma Research, 2018)
Leishmania is parasite protozoan of blood- tissue flagellates that causes the leishmaniasis disease. Pharmaceutical and therapeutic methods are used for the treatment of leishmaniasis. The use of pentavalent antimony drugs, cryosurgery, cryotherapy are therapeutic methods of leishmaniasis. In this study, we investigate patients with suspected cutaneous leishmaniasis who referred to the leishmaniasis treatment center of Dehloran city (Ilam province, Iran) during April 2015 to March 2016 and are treated with different medical checks. In this study, 410 patients with suspected leishmaniasis lesion were enrolled to the study which referred to the leishmaniasis treatment center of Dehloran city during April 2015 to March 2016. Suspected people were enrolled to the study after sampling and Giemsa staining and confirmation of leishmaniasis lesion. Patients were investigated after filling the forms and consent for follow-up treatment. The analysis of the results showed that 15.9%, 14.1%, 64.7% and 2.2% of patients are treated with systemic antimony, topical antimony, cryotherapy and topical antimony with cryotherapy, respectively and 0.4% of patients were under blank treatment and 2.7% of patients were treated with other leishmaniasis therapeutic methods. The used treatments for leishmaniasis depend on the severity, location, number and so on. Given that in 64.7% of patients, cryotherapy was performed alone so it is known that this type of treatment was a priority in 2015 because of the lack of Glucantim drug vials. Given that the subjects had leishmaniasis lesions in sensitive and non-sensitive points of body, they were exposed to different treatment regimes. Cooperation of patient with physician and patience until the end of the treatment process was another effective factor affecting the success of treatment in the study.